La pianificazione paesaggistica in Sardegna - Michele Ercolini; Emanuela Morelli (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The Sardinia Landscape Plan (PPR) is the first unitary Plan concerning the regional landscape. This is also the first time that a Landscape Plan involves the whole regional territory in a single process of knowledge and management of strategic resources. Moreover, the PPR represents a new experience thanks to its innovative approach towards the urban development.